Construction planning for the success of projects : a case study / Nor Sharena Mohd Amin Lou and Hafizah Mohd Latif - Mohd Amin Lou, Nor Sharena; Mohd Latif, Hafizah (2018)
In the construction of road, highways, airports or any other structures, the planning and scheduling of a project is an important part for every process of construction work proceeds smoothly. The aim of this research is to identify the process of project planning in road construction of Federal Road 12 (FR12) from Gambang, Pahang to Segamat, Johor-Phase 1 to complete the project in time and within the budget. The methods of this research were through the observation under a systematic and valuable construction schedule from Critical Path Method was carried out. The objectives of this research are determining the schedule of work through critical path method (CPM) and to investigate on tracking and updating of the schedule work. The Critical Path Method was developed through a software, Microsoft Project to build schedule contain document project tasks, duration, budget, date start and finish, percent complete, track progress until the project complete. The Gantt charts will automatically appear to show the illustrations of the project schedule and the dependency relationships between activities in the programming, planning and control of construction projects once the scheduling complete. There is no easy process to update the plan to get plan commitment. The research reveals that the construction schedule effects the whole construction from the start. The well-organized planning system can reduce the construction time, cost, labor and provided a more continuous work flow to increasing productivity of work.